482 Solriamfetol Titration & AdministRaTion (START): dosing and titration strategies in patients with narcolepsy starting solriamfetol. (3rd May 2021) - Thorpy, Michael; Hyman, Danielle; Parks, Gregory; Chen, Abby; Foley, Catherine; Ito, Diane; Singh, Haramandeep
Abstract: Introduction: Solriamfetol (Sunosi®), a dopamine/norepinephrine reuptake inhibitor, is approved (US and EU) to treat excessive daytime sleepiness (EDS) in adults with narcolepsy (75–150 mg/day) or obstructive sleep apnea (OSA) (37.5–150 mg/day). Previous research examined the use of solriamfetol in clinical trial settings but research in real-world settings was not previously conducted. This study characterized real-world dosing and titration with solriamfetol. Methods: This virtual, descriptive study included a quantitative retrospective patient chart review among US-based physicians prescribing solriamfetol. Target enrollment was 25 physicians treating patients with EDS associated with OSA or narcolepsy. Titration strategies were classified as de novo (no prior EDS medication), transition (switched/switching from existing EDS medications onto solriamfetol), or add-on (adding solriamfetol to current EDS medication). Results: Twenty-six physicians participated. Seventy patients with narcolepsy were analyzed (type 1, n=24; type 2, n=46; mean±SD age, 40±11 years; 57% female; 6 also had OSA); EDS was primarily moderate (59%) or severe (36%). Solriamfetol initiation was de novo for 19 (27%) patients, transition for 31 (44%), and add-on for 20 (29%). Most patients (86%) started solriamfetol at 75 mg; 11% and 3% started at 37.5 mg and 150 mg, respectively. The final/stable dose was 150 mg for 76% (53/70) of patients and 75 mg for 24% (17/70). Most patients (67%) had 1 dose adjustment to reach their final dose; 4% had 2 adjustments, 4% had 3 adjustments, and 24% had none. Mean±SD time to reach a stable dose was 15.1±11.8 days overall, 19.4±9.3 days with de novo treatment, 15.0±13.7 days for transition, and 11.9±8.6 days for add-on. Physicians most frequently considered EDS severity (44% of patients) when titrating. Among patients transitioning, 14/22 (64%) taking a wake-promoting agent (WPA) discontinued it abruptly while 5/9 (56%) taking a stimulant were tapered off. Physicians were overall likely (n=33, 47%) or very likely (n=30, 43%) to recommend their approach for similar patients. Conclusion: In a real-world study, the majority of physicians prescribing solriamfetol for patients with narcolepsy started at the 75-mg dose, tapered stimulants but abruptly discontinued WPAs, and made 1 adjustment to reach a stable dose across 15 days on average. Support (if any): Jazz Pharmaceuticals